Association between organophosphate flame retardant exposure and lipid metabolism: data from the 2013–2014 National Health and Nutrition Examination Survey - Cheng, Fu-Jen; Tsai, Kai-Fan; Huang, Kuo-Chen; Kung, Chia-Te; Huang, Wan-Ting; You, Huey-Ling; Li, Shau-Hsuan; Wang, Chin-Chou; Lee, Wen-Chin; Pan, Hsiu-Yung (Frontiers in Public Health, 2024)
Cardiovascular disease (CVD), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), National Health and Nutrition Examination Survey (NHANES), organophosphate flame retardants (OPFRs), triphenyl phosphate (TPhP), carboxylesterases (CEs), very-low-density lipoprotein (VLDL), tris(1,3-dichloro-2propyl) phosphate (TDCPP), solid-phase extraction (SPE), bis(1-chloro-2-propyl) phosphate (BCPP), bis(1,3-dichloro-2-propyl) phosphate (BDCPP), bis(2-chloroethyl) phosphate (BCEP), diphenyl phosphate (DPhP), body mass index (BMI), endoplasmic reticulum (ER), tris(2-butoxyethyl) phosphate (TBEP), polybrominated diphenyl ethers (PBDEs), polybrominated diphenyl ethers (PBDEs), cerebrovascular accident (CVA), limits of detection (LODs), lysophosphatidylcholine acyltransferase 3 (Lpcat3)